2012
DOI: 10.1104/pp.111.188920
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis TETRATRICOPEPTIDE THIOREDOXIN-LIKE Gene Family Is Required for Osmotic Stress Tolerance and Male Sporogenesis      

Abstract: TETRATRICOPEPTIDE THIOREDOXIN-LIKE (TTL) proteins are characterized by the presence of six tetratricopeptide repeats in conserved positions and a carboxyl-terminal region known as the thioredoxin-like domain with homology to thioredoxins. In Arabidopsis (Arabidopsis thaliana), the TTL gene family is composed by four members, and the founder member, TTL1, is required for osmotic stress tolerance. Analysis of sequenced genomes indicates that TTL genes are specific to land plants. In this study, we report the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 49 publications
4
64
0
Order By: Relevance
“…It is a gene proven to be involved in the resistance of soybean to SCN Lakhssassi et al, 2012;. This study confirmed those earlier findings and showed the complexity of the introgressed region.…”
supporting
confidence: 80%
“…It is a gene proven to be involved in the resistance of soybean to SCN Lakhssassi et al, 2012;. This study confirmed those earlier findings and showed the complexity of the introgressed region.…”
supporting
confidence: 80%
“…Previous studies in the plant model Arabidopsis thaliana have shown that a TPR protein family named Tetratricopeptide repeat thioredoxin-like (TTL), formed by four members. TTL1, TTL3, and TTL4, but not TTL2, presented an additive effect in response to osmotic stress tolerance and are essential for root growth and integrity, while all present the same amino acid sequence length with high identity12. This is an example of a duplicated gene resulting in a truncated protein (50 aa less) that presents an additive effect in resistance to a pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the TPR domain facilitates specific interactions with a partner protein(s)11. Moreover, TPR domains also play important roles in aspects of plant development; being essential for gametophytic viability as well as root growth and integrity under osmotic stress12. In addition, a different member of TPR containing proteins, TTL3 , was found to interact with the constitutively active VH1/BRL2, a protein homologous to the brassinosteroid receptor BRI1, and play a role in vasculature development13.…”
mentioning
confidence: 99%
“…Within this dataset, we identified four transcription factors including soybean homologues of AtBZIP9, AtTTL1, AtIAA17 and AtIDD2. While roles in defence have not been demonstrated for AtBZIP9 and AtIDD2, AtTTL1 is required for osmotic stress tolerance (Lakhssassi et al 2012) and AtIAA17 increases tolerance to Plasmodiophora brassicae (Kazan and Manners 2009). …”
Section: The Role Of Transcription Factors In Mediating Defence Respomentioning
confidence: 99%